Numerival Simulation of Vortex Dynamics in superconductor with Using Time Dependent Ginzburg Landau Equation - Harsojo Harsojo; Pekik Nurwantoro; Muslim Muslim (Indonesian Journal of Physics, 2004)
The study of vortex dynamics in type II superconductors has drawn attention many people for the last ten years especially since the discovery of high Tc superconductor materials. This basics information are importance to study the role of vortex dynamics in some of the superconductor quantities. In this paper the time dependent Ginzburg-Landau (TDGL) equations has been used to describes the vortex dynamics under an external magnetic field varies linearly with time limited to two dimension. From the numerical solution we inspect the existence of the vortex quantization, the properties of magnetization of the sample, and calculate the number of vortices based on the related supercurrent and free energy produced in associated the related order parameter. The calculation result indicates clearly the existence of vortex quantization related to the appearance of oscillation of magnetization as a function of external field. The possibility of studying the effect of adding pinning and holes together with the varying of the temperature are discussed.